Association between radicular low back pain and constipation: a retrospective cohort study using a real-world national database. (26th September 2021) - Trager, Robert James; Mok, Shaffer R.S.; Schlick, Kayla J.; Perez, Jaime A.; Dusek, Jeffery A.
Abstract : Supplemental Digital Content is Available in the Text. The results from a large sample suggest there is no clinically significant increase in odds of constipation in lumbosacral radiculopathy compared with nonradicular low back pain. Abstract: Introduction: Previous observational studies have reported an association between lumbosacral radiculopathy (LSR), a form of low back pain (LBP) with nerve root involvement, and constipation. However, it is unclear whether this association is due to confounding variables such as comorbidities and medications. Objectives: This study explores the possible association between LSR and constipation, with the hypothesis that adults with LSR have increased odds of developing constipation compared with those with nonradicular LBP. Methods: Adults aged 18 to 49 years with incident LSR and nonradicular LBP were identified from a national 70 million patient electronic health records network (TriNetX). Propensity score matching (PSM) was used to control for covariates and determine the odds ratio (OR) of constipation over a 1-year follow-up. Lumbar stenosis, cauda equina syndrome, and inflammatory bowel diseases were excluded. Results: After PSM, 503, 062 patients were in each cohort. Before PSM, the likelihood of constipation was identical between cohorts (LSR 10.8% vs 10.9%; OR [confidence interval] = 0.99 [0.98-1.0], P = 0.251). This association was unchanged after PSM (LSR 10.8% vs 11.1%; OR [confidence interval] = 0.98 [0.97-0.99]; P = 0.003). Conclusions: The study hypothesis can be refuted given that the OR approximated the null in a large propensity-matched sample. Patients with LSR have equivalent odds of constipation compared with those with nonradicular LBP, suggesting that LSR is not a direct cause of constipation. The similar risk of constipation between cohorts could be explained by factors common to LBP in general, such as pain severity, physical inactivity, and constipating medications.